LncRNA ENST00000453774.1 contributes to oxidative stress defense dependent on autophagy mediation to reduce extracellular matrix and alleviate renal fibrosis. Issue 6 (14th October 2018) - Xiao, Xiangcheng; Yuan, Qiongjing; Chen, Yusa; Huang, Zhihua; Fang, Xi; Zhang, Haixia; Peng, Ling; Xiao, Ping
Abstract: Although long noncoding RNA (LncRNA) are important players in the initiation and progression of many pathological processes, the role of LncRNAENST00000453774.1 (LncRNA 74.1) in renal fibrosis still remains unclear. Lentivirus mediated LncRNA 74.1 overexpressing HK2 cells and overexpression mice models were constructed. HK2 cells induced by transforming growth factor‐β (TGF‐β) in vitro, and the mice UUO model in vivo were used to simulate renal fibrosis. The expression of LncRNA 74.1 was significantly downregulated in the TGF‐β‐induced HK‐2 cell fibrosis and clinical renal fibrosis specimens. LncRNA 74.1 overexpression obviously attenuated renal fibrosis in vitro and unilateral ureteral obstruction‐induced renal fibrosis in vivo. LncRNA 74.1 promoted reactive oxygen species defense by activating prosurvival autophagy then decreased ECM‐related proteins fibronectin and collagen I involved in renal fibrosis. We also found that Nrf2‐keap1 signaling played important roles in the remission of ECM mediated by LncRNA 74.1. This study indicates that LncRNA 74.1 downregulation would contribute to renal fibrosis and its overexpression might represent a novel anti‐fibrotic treatment in renal diseases. Abstract : LncRNA 74.1 downregulation would contribute to renal fibrosis. Overexpression of LncRNA 74.1 might promote ROS defense via Nrf2‐keap1/HO‐1/NQO‐1 signaling by activating prosurvival autophagy then decrease the ECM related proteins, fibronectin and collagen I, involved in renal fibrosis.